A cryogenic scintillation UCN detector for a neutron EDM experiment - Lynch, A (2014)
The observed imbalance of matter and anti-matter in the universe is one of physics' most fundamental unresolved questions. The leading theories to explain this imbalance require CP violation, and the neutron electric dipole moment (nEDM) is a sensitive parameter in its determination. Many new theories of physics beyond the standard model can be constrained or ruled-out by setting limits on the nEDM. Many next generation nEDM experiments require Ultra Cold Neutrons (UCN), produced in superfluid helium. One such experiment is cryoEDM. This thesis explores various types of UCN detection technologies applicable to cryoEDM or any high-density high-efficiency cryogenic nEDM experiment. Cryogenic Phonon Scintillation detectors (CPSD) are modified for this application by operating at 500 mK, and by using a titanium transition edge sensor for phonon signal readout. A CPSD is stabilised in the transition using a novel infra-red light feedback system which reduced the response time to O(100 μs). The detector is characterised and calibrated using an 241Am α source. It was found to operate reliably at this elevated temperature and measure an alpha spectrum with 11% resolution at 5.5 MeV. Scintillators are identified as a promising technology for UCN detection at low temperature. Suitable materials that are bright with fast decay times and low γ sensitivity are studied in the temperature range 300 - 6 K. Their light yield to alpha excitation, their decay time characteristics and spectroscopic properties under VUV excitation are investigated. This study includes the first comprehensive investigation of the luminescence properties of plastic scintillators and of 6LiF/ZnS(Ag) down to 6 K. It is found that there is no degradation of the luminescence or kinetic properties of these materials across the whole temperature range, revealing them as suitable cryogenic detector materials. Using a plastic scintillator, a prototype UCN detector for operation in liquid helium is designed, manufactured and tested. It is read out using WLS optical fibres to a room temperature photomultiplier. The detector is successfully tested with cold neutrons at the ISIS neutron science facility and found to effectively measure neutrons, with a signal that is clear from background. Recommendations are made for its integration into a cryogenic neutron EDM experiment. This low-cost detector offers a promising method for the passive detection of UCN in a challenging cryogenic environment, with minimal electric interference and low background sensitivity. This technology offers the potential for improved UCN detection efficiency and thus improved sensitivity of the measurement of the neutron EDM.